THE ROLE OF ANTIHYPERTENSIVE MEDICATIONS IN THE MANAGEMENT OF CEREBROVASCULAR COMPLICATIONS IN ARTERIAL HYPERTENSION - N. U. Makhkamova; A. I. Khodzhaev; A. A. Khodzhaev; N. R. Salimova; M. R. Shakirov; F. A. Sarmanov (Российский кардиологический журнал)
.